PENGARUH KOMPETENSI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT TUNAS MUDA SERUNI - Sulastri, Atih; Karmelia, Mila (Jurnal Inspirasi Ilmu Manajemen, 2025)
This study aims to analyze the influence of competence, motivation, and work discipline on employee performance. The research was conducted at PT Tunas Muda Seruni with a total population of 35 employees. The sampling technique employed was non-probability sampling using a saturated sampling approach, in which all members of the population were included as research samples. Data were collected through a questionnaire utilizing a Likert scale (1–5). The data analysis technique used was multiple linear regression analysis. The findings indicate that competence, motivation, and work discipline each have a positive and significant effect on employee performance.